2023
DOI: 10.1111/fare.12934
|View full text |Cite
|
Sign up to set email alerts
|

A focus on fathers with intellectual disabilities and child protection

Abstract: ObjectiveThe article presents research findings whose aim was to understand the lived experiences of fathers with intellectual disabilities referring to child protection proceedings they were involved in as fathers and the meanings ascribed to these experiences.BackgroundParents with intellectual disabilities face a high risk of having their children removed and being involved in child protection procedures. The overwhelming majority of studies focus on mothers. Little do we know about fathers' perspective.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The collection includes a review article (Y. Wang & He, 2024), two quantitative studies (Armah et al, 2024;Kang et al, 2024), three qualitative works ( Cwirynkało & Parchomiuk, 2024;Daniel, 2024;A. Liu et al, 2024), and one evaluation study (Avey et al, 2024).…”
Section: Hhh Issue Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The collection includes a review article (Y. Wang & He, 2024), two quantitative studies (Armah et al, 2024;Kang et al, 2024), three qualitative works ( Cwirynkało & Parchomiuk, 2024;Daniel, 2024;A. Liu et al, 2024), and one evaluation study (Avey et al, 2024).…”
Section: Hhh Issue Articlesmentioning
confidence: 99%
“…Fathers face other issues. For example, Cwirynkało and Parchomiuk (2024) explored the lived experiences of fathers with intellectual disabilities when interacting with child protective services in Poland. Consistent with the use of diverse social supports used by fathers in the Cwirynkało and Parchomiuk (2024) study, Augsberger et al (2021) suggested additional supports of persons with disabilities to include access to parenting programs and comprehensive services to address risk factors while promoting the parental strengths.…”
Section: Hhh Issue Articlesmentioning
confidence: 99%